The Horizontal Curved Geometric Redesign on Jalan Kayu Api Kuala Penaso, Riau Using the Autocad Civil 3d® Method - Syafiq Human Maulana; Andri Irfan Rifai; Muhammad Isradi (Indonesian Journal of Multidisciplinary Science, 2022)
Jalan Kayu Api Kuala Penaso, Talang Muandau district, Bengkalis Regency, is a section of road that connects Beringin Village to the district capital, with straight road conditions and has several sharp bend points. Horizontal alignment (road traffic) is a crucial point in geometry planning. It can produce road shapes that can be utilized for traffic operations quickly, smoothly, safely, comfortably, and efficiently with two different types of bends. The first bend uses the SCS type (Spiral – Circle – Spiral) with a radius of 800 m. The second bend uses the SS type (Spiral – Spiral) with a radius of 400 m. Plan speed (Vr) is 80 km/h, with a maximum slope of 0.06 and a transverse tightness (fmax) of 0.15.